A need for emotionally intelligent leaders in educational institutions: A review of the effects of leadership style on burnout teachers - Dishari, Samira; AlAfnan, Mohammad Awad (World Journal of Vocational Education and Training, 2024)
For the three pillars of education: teacher, student, and curriculum to function properly, leadership plays an intrinsic role. Academic leadership aims to provide the right working environment for proper teaching and learning to take place. Thus, leadership style has a paramount effect on teachers who consequently affect students and ensure proper instruction to all aspects of curriculum. This article review aims to unfold the dynamics of this relationship. In particular the researchers will attempt to explore the role of transformational leadership which also displays qualities of emotional intelligence on reducing the occurrence of the syndrome of burn out among teachers. Sample of empirical, experimental and case studies that examined the correlation between symptoms and causes of job burnout among teachers and the style of leadership practiced will be presented. Seven of which were examined to verify the impact of leadership in a school setting and three others to examine the same impact but in a university context. As a result, researchers assert that in traditional leadership where qualities of empathy, social awareness, and management of relationships are missing, job burnout cases among teachers increase. Finally, a recommendation to introduce emotional intelligence skills into academic leaders' training programs was made. The findings of this study shall serve leaders and policymakers in the teaching and learning sector in a way that would benefit them and assist their subordinates in avoiding burnout and achieve greater heights.